2020
DOI: 10.1186/s12889-020-09961-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of the Chinese public with respect to coronavirus disease (COVID-19): an online cross-sectional survey

Abstract: Background Coronavirus disease (COVID-19) has become a pandemic. The knowledge, attitudes, and practices (KAP) of the public play a major role in the prevention and control of infectious diseases. The objective of the present study was to evaluate the KAP of the Chinese public and to assess potential influencing factors related to practices. Methods A cross-sectional online survey was conducted in China in February 2020 via a self-designed questionnaire comprising 33 questions assessing KAP. Results For the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
65
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 11 publications
23
65
4
5
Order By: Relevance
“…Concerning to study responders’ attitude towards the COVID-19 pandemic in Saudi Arabia, the highest level of good attitude about the COVID-19 pandemic was among married participants and those from the Western Province of Saudi Arabia with bachelor’s degrees. This finding is similar to other studies with higher KAP among married individuals [ 24 , 25 ]. It was thought that married individuals had a higher level of positive attitudes towards COVID-19 as they cared for close family members, including young children [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concerning to study responders’ attitude towards the COVID-19 pandemic in Saudi Arabia, the highest level of good attitude about the COVID-19 pandemic was among married participants and those from the Western Province of Saudi Arabia with bachelor’s degrees. This finding is similar to other studies with higher KAP among married individuals [ 24 , 25 ]. It was thought that married individuals had a higher level of positive attitudes towards COVID-19 as they cared for close family members, including young children [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is similar to other studies with higher KAP among married individuals [ 24 , 25 ]. It was thought that married individuals had a higher level of positive attitudes towards COVID-19 as they cared for close family members, including young children [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that individual demographic characteristics had an impact on their KAP, which is consistent with previous studies (24)(25)(26). Educational level and place of residence were the influencing factors of respondents' knowledge, which was also in line with the law of low educational level in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…First, the survey was conducted during the winter holidays, in which the students might have lower levels of academic pressures and mental health symptoms ( Wang et al, 2020b ). Second, since the outbreak of COVID-19, the government had delivered the knowledge of epidemic through various channels, such as television, internet, and WeChat ( Gao et al, 2020 ), which could help adolescents mitigate their fears and anxiety toward the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%